Psilocybin-Assisted Therapy for Alcohol Use Disorder: A Systematic Review of Clinical Evidence - Laura Schäffert; Human-Friedrich Unterrainer (Psychoactives, 2026)
Background: Alcohol use disorder (AUD) remains a leading contributor to global morbidity, yet conventional treatments often yield suboptimal outcomes and high relapse rates. Psilocybin-assisted therapy has re-emerged as a potential intervention for substance use disorders, but its effectiveness and safety in AUD specifically remain to be comprehensively evaluated. Objective: To review and synthesize available evidence on the efficacy and safety of psilocybin-assisted therapy in adults with AUD. Methods: A systematic search of PubMed, PsycNet, Cochrane Library, and EuropePMC was conducted on 16 June 2025 for studies published between January 2004 and 16 June 2025. Eligible studies included English-language clinical trials investigating psilocybin-assisted therapy in adults with AUD, including randomized controlled trials and proof-of-concept designs. Due to heterogeneity in study design and outcome measures, results were synthesized narratively. Results: Three eligible studies were identified. Overall, psilocybin-assisted therapy was associated with reductions in heavy drinking days and showed an acceptable safety profile in the context of controlled research settings with highly selected participants. However, findings on abstinence rates and relapse prevention were mixed, with some studies reporting no significant differences between psilocybin and control conditions. Conclusions: Preliminary evidence suggests that psilocybin-assisted therapy may reduce heavy alcohol consumption in some individuals with AUD, but the evidence base is very small and findings are inconsistent across studies. The available data are insufficient to establish clinical effectiveness or to support routine implementation. Larger randomized trials with standardized protocols, longer follow-up, and independent replication are required before conclusions about clinical utility can be drawn.